1991
DOI: 10.1227/00006123-199101000-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Continuous Drainage of Cerebrospinal Fluid in Patients with Subarachnoid Hemorrhage: A Retrospective Analysis of 108 Patients

Abstract: The effects of continuous drainage of cerebrospinal fluid (CSF) on vasospasm and hydrocephalus were analyzed retrospectively in 108 patients with subarachnoid hemorrhage (SAH) who were operated on for ruptured aneurysms within 48 hours of their onset. Ninety-two of these patients underwent a procedure for CSF drainage (cisternal drainage, ventricular drainage, lumbar drainage, or a combination of these). The duration, the total volume, and the average daily volume of CSF drainage were 10.4 ± 7.0 days (mean ± S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 0 publications
1
54
0
1
Order By: Relevance
“…In contrast, cisternal CSF drainage and irrigation has been associated with a higher rate of permanent CSF diversion with the volume of drainage proportional to this rate. 10,11,23 It is unclear why lumbar drainage did not increase the occurrence of long-term hydrocephalus. Acute and chronic hydrocephalus is thought to result from tentorial/ventricular obstruction and blockage of arachnoid granulations with blood, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, cisternal CSF drainage and irrigation has been associated with a higher rate of permanent CSF diversion with the volume of drainage proportional to this rate. 10,11,23 It is unclear why lumbar drainage did not increase the occurrence of long-term hydrocephalus. Acute and chronic hydrocephalus is thought to result from tentorial/ventricular obstruction and blockage of arachnoid granulations with blood, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…6 -9 Studies investigating cisternal drainage have reported mixed results. 6,10,11 Cisternal drains and intrathecal thrombolysis are difficult to administer and not without morbidity. There has been some evidence to suggest that drainage of cerebrospinal fluid (CSF) through the lumbar cistern may be of some benefit in reducing the prevalence of DIND.…”
mentioning
confidence: 99%
“…Measurement of sequential changes of oxyhemoglobin concentration showed decreases by day 5 and maintenance at a very low level with urokinase irrigation, but increases peaking on day 9 without urokinase irrigation. 13) Our previous report 9) and others 1,12,15) have indicated that duration of CSF drainage is a statistically significant predictor of late hydrocephalus after SAH. Continuous CSF drainage may promote occlusion of physiological CSF pathways.…”
Section: Discussionmentioning
confidence: 88%
“…Excessive drainage of CSF is related to a greater incidence of cerebral infarction and occurrence of late hydrocephalus. 1,12) It is possible that such cerebral infarction is causally related to the occurrence of late hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation